PENDIDIKAN DAN PERGERAKAN NASIONAL: BANYUWANGI AWAL ABAD XX - Bahagio Raharjo (Handep: Jurnal Sejarah dan Budaya, 2022)
Modern education in Banyuwangi, which was established by the government, firstly appeared in 1819 in the form of the Europeesche Lagere School (ELS), approximately two years after the first school has founded in the Dutch East Indies. The existence of this school is inseparable from the interests and needs of the government to prepare skilled government employees. The existing schools were not well developed even though the need for modern schools increased. The enactment of the ethical policy provided an opportunity for non-government parties. Subsequently, schools established by Indo-European, Arab, and Chinese entrepreneurs, and national movement organization. This paper studies the dynamics of their roles in founding a modern school in Banyuwangi during the era of ethical policy. This study used historical methods to explain the education and policies that encouraged the nongovernment sector’s efforts at that time in actively establishing schools for their respective groups. The study found that ethical policy opened opportunities and strengthened the existence of parties outside the government to establish schools in Banyuwangi and develop modern education. The changes were in the strengthening of plantation companies that promoted the opening of new areas, the economic crisis, and the politics of segregation demanded the availability of schools for all groups.